Dual spinneret electrospun polyurethane/pva-gelatin nanofibrous scaffolds containing cinnamon essential oil and nanoceria for chronic diabetic wound healing: preparation, physicochemical characterization and in-vitro evaluation - ŞAHİN, ALİ; GÜNDÜZ, OĞUZHAN (My University, 2022)
© 2022 by the authors. Licensee MDPI, Basel, Switzerland.In this study, a dual spinneret electrospinning technique was applied to fabricate a series of polyurethane (PU) and polyvinyl alcohol–gelatin (PVA/Gel) nanofibrous scaffolds. The study aims to enhance the properties of PU/PVA-Gel NFs loaded with a low dose of nanoceria through the incorporation of cinnamon essential oil (CEO). The as-prepared nCeO2 were embedded into the PVA/Gel nanofibrous layer, where the cinnamon essential oil (CEO) was incorporated into the PU nanofibrous layer. The morphology, thermal stability, mechanical properties, and chemical composition of the produced NF mats were investigated by STEM, DSC, and FTIR. The obtained results showed improvement in the mechanical, and thermal stability of the dual-fiber scaffolds by adding CEO along with nanoceria. The cytotoxicity evaluation revealed that the incorporation of CEO to PU/PVA-Gel loaded with a low dose of nanoceria could enhance the cell population compared to using pure PU/PVA-Gel NFs. Moreover, the presence of CEO could inhibit the growth rate of S. aureus more than E. coli. To our knowledge, this is the first time such nanofibrous membranes composed of PU and PVA-Gel have been produced. The first time was to load the nanofibrous membranes with both CEO and nCeO2. The obtained results indicate that the proposed PU/PVA-Gel NFs represent promising platforms with CEO and nCeO2 for effectively managing diabetic wounds.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Biyokimya; Alkoloidler; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Chemistry; Biochemistry; Alcaloides; Natural Sciences; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Moleküler Biyoloji ve Genetik; Yaşam Bilimleri (LIFE); KİMYA, MULTİDİSİPLİNER; Temel Bilimler (SCI); BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); CHEMISTRY, MULTIDISCIPLINARY; CHEMISTRY; Natural Sciences (SCI); Biochemistry, Genetics and Molecular Biology (miscellaneous); Clinical Biochemistry; Cancer Research; Molecular Biology; Drug Discovery; Aging; General Biochemistry, Genetics and Molecular Biology; Structural Biology; Chemistry (miscellaneous); General Chemistry; Physical Sciences; nanoceria; dual spinneret electrospinning; PU; PVA-gelatin-based nanofibrous scaffolds; diabetic wound healing; ANTIMICROBIAL PROPERTIES; ANTIBACTERIAL ACTIVITY; COMPOSITE NANOFIBERS; NANOPARTICLES; OXIDE; FILMS; MECHANISM; MEMBRANES; COMBINATION; DRESSINGS; PU/PVA-gelatin-based nanofibrous scaffolds; nanoceria; dual spinneret electrospinning; PU/PVA-gelatin-based nanofibrous scaffolds; diabetic wound healing